Monasticism in Eastern Europe and the former Soviet Republics - Murzaku, Ines Angjeli (Routledge religion, society and government in Eastern Europe and the Former Soviet States, 2016)
"This book looks at Eastern and Western monasticism's continuous and intensive interactions with society in Eastern Europe, Russia and the Former Soviet Republics. It discusses the role monastics played in fostering national identities, as well as the potentiality of monasteries and religious orders to be vehicles of ecumenism and inter-religious dialogue within and beyond national boundaries. Using a country-specific analysis, the book highlights the monastic tradition and monastic establishments. It addresses gaps in the academic study of religion in Eastern European and Russian historiography and looks at the role of monasticism as a cultural and national identity forming determinant in the region"--Publisher info